PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP MANAJEMEN PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2017-2019) - Sailawati Sailawati; Marwanto Marwanto; Febrianti Febrianti (Jurnal Eksis, 2021)
This study aims to determine the effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on Tax Management. The analytical method used is multiple linear regression analysis. The sample of this research is the annual report of 20 companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The result of this study indicates that the Board of Commissioners and Audit Committe have a significant effect on Tax Management. Simultaneously the GCG and CSR have a significant effect on Tax Management. Then, the Compensation, CSR and the Precentage of Independent Commissioners do not have a significant effect on Tax Management. The limitation in this study is that the company’s annual report data is incomplete and only based on Cash Effective Tax Rate (CETR) to measure the company’s effective tax rate. Keywords: Cash Effective Tax Rate, Good Corporate Governance, Corporate Social Responsibility.